Lateral column lengthening augmented by medial split tibialis posterior tendon advancement for the treatment of symptomatic flexible flatfeet - Ahmed, Amin Abdelrazek Youssef; Michael, Mina (International Journal of Research in Orthopaedics, 2019)
Background: Management of Idiopathic flexible pes planus (IFPP) is debatable. Surgery is rarely indicated for flexible flatfoot. The goal of the surgery should be always to treat symptomatic patients and not to alter the shape of the foot. There are numerous options for surgical treatment in children and adolescents including subtalar arthroereisis or osteotomy with or without soft tissue procedures. Methods: Between June 2013 to December 2017, twenty eight feet in sixteen patients (9 boys, 7 girls) were included in this study. Twelve cases were operated bilaterally, three in the right foot and one in the left side. The mean age of the patients was 8.36±1.704 years (6-12 years). Calcaneal lengthening osteotomy was done with an oscillating saw about 1.5 cm proximal to the calcaneocuboid joint. Usually, 8-10 mm autologous bone graft from iliac crest was sufficient and fixed by K wires. Half of the tibialis posterior tendon after splitting with a periosteal flap from the navicular was then advanced distally until clinical restoration of the medial arch was then performed. Results: Radiographic analysis revealed significant improvements in talo-first metatarsal, calcaneal pitch, talocalcaneal angles in lateral radiographs, and talo-first metatarsal and talonavicular coverage angles in AP radiographs. All patients were evaluated at final follow-up visits. Preoperative mean AOFAS score increased significantly from 64.04±8.867 (range: 50 to75) to 94.11±3.765 (90-100). Conclusions: It is concluded that Evans calcaneal lengthening osteotomy augmented by spilt tibialis posterior tendon advancement is an excellent procedure in the management of IFPP.